PENGARUH JARAK SUMUR GALI DENGAN SEPTIC TANK TERHADAP KANDUNGAN BAKTERI COLIFORM PADA AIR SUMUR GALI - Pujiati, Rahayu Sri; Pebriyanti, Dwi Ochta (FKM - UNEJ, 2010)
The existence of coliform bacteria on water sources can indicate that the water has been contaminated by material of human waste. This research is aimed at identifying the influence of construction of drug water well, construction of septic tank, and distance between drug water well and septic tank on the amount of coliform bacteria of water of dug well by using analytical survey method. The number of samples involved were 92 dug wells. Data obtained were analyzed by using linear regression test of significance level (Î±) of 5%. The research findings showed probability value of 0.001 for dug well construction, 0.000 for septic tank construction and 0.000 for distance between dug well and septic tank. Since the probability value of each variable was less than significance level (Î±) of 5%, dug well construction, septic tank construction and distance between dug well and septic tank significantly influenced the amount of coliform bacteria of dug well water. Keywords: dug well, septic tank, distance, the coliform bacteria